2021
DOI: 10.3390/agronomy11020265
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Application of Ulva rigida Water Extracts Improves Salinity Tolerance in Wheat (Triticum durum L.)

Abstract: This study investigated the effect of seaweed extract (SWE) sprays obtained from Ulva rigida on wheat plants (Triticum durum L., variety Karim) grown under salt stress conditions for six weeks. Three levels of NaCl (0, 34.22, 68.44 mM) and four different concentrations (0, 12.5, 25 and 50%) of Ulva rigida as a water extract were applied. The obtained results indicated that seaweed treated plants showed higher ability to tolerate salt stress (34.22 or 68.44 mM of NaCl) by a significant (p < 0.05) increase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 56 publications
5
14
0
Order By: Relevance
“…Our results agreed with those of Bacha et al (2017) [ 23 ], in which a decrease in the chlorophyll content of Solanum lycopersicum that was subjected to salinity stress was observed. The same results were also found by Latique et al (2021) [ 24 ]. The authors investigated the effect of salt stress on wheat ( Triticum Durum L. ) and the ability of Ulva rigida water extract to improve salinity tolerance in wheat ( Triticum Durum L. ).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Our results agreed with those of Bacha et al (2017) [ 23 ], in which a decrease in the chlorophyll content of Solanum lycopersicum that was subjected to salinity stress was observed. The same results were also found by Latique et al (2021) [ 24 ]. The authors investigated the effect of salt stress on wheat ( Triticum Durum L. ) and the ability of Ulva rigida water extract to improve salinity tolerance in wheat ( Triticum Durum L. ).…”
Section: Resultssupporting
confidence: 89%
“…Our study showed that the application of C. oxyacantha extract as a biostimulant enhanced antioxidant activities. The same result was obtained by Latique et al (2021) [ 24 ]. The authors claimed that Ulva rigida extract enhances the antioxidant enzyme activities of wheat under salinity stress.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast, PC decreased in the absolute control and S. stolonifolium amended soil compared to the absolute cadmium treated groups (T1 and T5). Our finding is in line with previous research conducted on antioxidant stimulation of seaweed on wheat (Latique et al, 2021). Increased PBT, TT and GSH in S. stolonifolium amended soil may be due to the enormous number of bioactive molecules from S. stolonifolium that stimulates key enzymes for the biosynthesis of thiol containing molecules.…”
Section: Sulfhydryl Containing Compoundssupporting
confidence: 92%